DISTRIBUTION OF INHERITANCE IN THE PRENGKENIN TRADITION. The Muslim Community in Bagik Payung Timur Village, West Nusa Tenggara. - Lalu Haidir Ali (Universitas Islam Negeri Ar-Raniry, 2022)
Distribution of Inheritance in the Prengkenin Tradition to the Muslim Community in Bagik Payung Timur Village, West Nusa Tenggara The distribution of inheritance through the Prengkenin custom is the designation or attribution of certain assets to heirs by parents which will be owned immediately or after the parents die. The distribution of inheritance through prengkenin produces two patterns, namely, a) grants, designating certain assets that can be owned immediately, and b) wills, assets that will be owned after parents die. The share of each heir is determined in a family meeting witnessed by traditional leaders with the aim of being obedient, good, solah-solah (getting along with siblings) and spur-pacu (maintaining good manners). This illustrates an attitude of tolerance and mutual respect. The division between boys and girls uses the principle of mama meonggok, nina nyenyion (men carry, women carry). It describes the role of a child which will then affect the number of parts. While the reasons for the BPT Village Community to distribute inheritance through prengkenin are, a) avoiding conflicts between heirs in the future. b) distributive justice c) dissatisfaction with the traditional inheritance fiqh system.